Byzantium : beyond the cliche : A Conversation with Maria Mavroudi. - Burton, Howard (Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Maria Mavroudi, Professor of History at UC Berkeley. Maria Mavroudi specializes in the study of the Byzantine Empire and this wide-ranging conversation provides a detailed exploration of her extensive research on the Byzantine Empire and how it has repeatedly been undervalued by historians despite having been a military and cultural powerhouse for more than a millennium.This carefully-edited book includes an introduction, Beyond the High-School Narrative, and questions for discussion at the end of each chapter. How.
Description based upon print version of record.
Keywords: Mavroudi, Maria V. -- Interviews.; Byzantine Empire.; Greece.; Ancient.; HISTORY.; Rome.; Medieval.; Byzantine Empire; Interviews